Tumor Glómico (Hemangiopericitoma) del Mediastino Posterior - Aguilar C., Polinéstor (1959)
A case of glomus tumor (hemangiopercytoma) is reported. It was localized in the posterior mediastinum at the level of the 5th. intervertebrla space. The tumor was well encapsulated. On the histological examination four fairly well noted layers are described: angiomatous, arterial, glomic and hemangioperiteliomatous. Elastic fibers in all the vascular structures are not found. Muscle is only found in the glomic layer. All the vessels and capillaries are rich in reticulin fibers. A nodular formation, described by Eichwald in the Capillary Hemangiomas, is found. It is formed by reticular fibers. Nervous fibers are seen only in the angiomatous and arterial layers. We feel that the Hemangiopericytoma is a sinnonimous of Glomus Tumor. To date (1 year) no clinical signs of recurrence or radiological chest abnormalities.